2019
DOI: 10.1177/0379572119841961
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Opportunities for Improved Exclusive Breast-Feeding Practices in Tanzania: Household Trials With Mothers and Fathers

Abstract: Background: Effective promotion of exclusive breast-feeding (EBF) is needed to improve child nutrition and survival. Objective: We explored barriers and facilitators to EBF in rural Tanzania and assessed parents’ willingness and ability to try specific recommended EBF practices plus strategies for men to support breast-feeding. Methods: We conducted Trials of Improved Practices in 36 households with infants <6 months. Fathers participated in focus group discussions on ways to support breast-feeding. Fathers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 31 publications
4
56
0
7
Order By: Relevance
“…Mother’s formal (employment) and informal work schedules [ 26 33 ] 1.1.2 Perceived breast milk insufficiency [ 26 28 , 31 – 38 ] 1.1.3 Concerns of effects on mother’s appearance [ 28 , 31 , 38 , 39 ] 1.1.4 Poor understanding/lack of awareness of EBF benefits [ 32 , 34 , 35 , 40 ] 1.1.5 Being HIV positive or fear of transmitting HIV infection to the child [ 31 , 32 , 34 , 36 ] 1.1.6 Schooling or resuming school or work [ 29 , 33 , 36 , 37 , 41 ] 1.1.7 Poor maternal nutrition [ 29 , 32 34 , 41 ] 1.1.8 Maternal perceived discomfort and embarrassment [ 26 , 28 , 29 , 31 , 33 , 39 ] 1.1.9 Reluctance to breastfeed in public/disapproval of public breastfeeding [ 29 , 31 , 33 , 37 ] 1.1.10 Refusal of mothers to breastfeed for several other reasons …”
Section: Resultsmentioning
confidence: 99%
“…Mother’s formal (employment) and informal work schedules [ 26 33 ] 1.1.2 Perceived breast milk insufficiency [ 26 28 , 31 – 38 ] 1.1.3 Concerns of effects on mother’s appearance [ 28 , 31 , 38 , 39 ] 1.1.4 Poor understanding/lack of awareness of EBF benefits [ 32 , 34 , 35 , 40 ] 1.1.5 Being HIV positive or fear of transmitting HIV infection to the child [ 31 , 32 , 34 , 36 ] 1.1.6 Schooling or resuming school or work [ 29 , 33 , 36 , 37 , 41 ] 1.1.7 Poor maternal nutrition [ 29 , 32 34 , 41 ] 1.1.8 Maternal perceived discomfort and embarrassment [ 26 , 28 , 29 , 31 , 33 , 39 ] 1.1.9 Reluctance to breastfeed in public/disapproval of public breastfeeding [ 29 , 31 , 33 , 37 ] 1.1.10 Refusal of mothers to breastfeed for several other reasons …”
Section: Resultsmentioning
confidence: 99%
“…Hasil penelitian menjelaskan dengan adanya dukungan dari suami, maka emosional ibu akan stabil dan termotivasi untuk memberikan bayinya dengan gizi yang baik yaitu ASI eksklusif, dibuktikan dengan sangat sedikit bayi yang diberikan makanan tambahan setelah diberikan edukasi kepada para suami untuk memberikan dukungan kepada istri untuk memberikan ASI secara eksklusif (Matare et al, 2019).…”
Section: Gambaranunclassified
“…The breastfeeding practice is a complex process that goes beyond biological determinism, and the woman’s decision to breastfeed or not also involves social, cultural, economic, and psychological factors ( 5 ) . A study carried out in the Federal District (Brazil) found that the causes for early weaning were related to the beliefs of weak milk and to the women’s need to return to work ( 6 ) .…”
Section: Introductionmentioning
confidence: 99%